Análise da formação de bandas de cisalhamento por meio de corpos de prova de tração especiais - Arisson Carvalho de Araujo (2009)
The present paper has as main purpose analyze the formation of shear bands in metallic sheets of steel low carbon (SAE 1006) submitted to uniaxial tension test. This verification has been made through the numerical analysis using the software Deform2D, as well as the realization of physical tests by the tensions test specimen notched with varied geometries. It has been risen the curve of flow and the anisotropy of the material used for the realization of numerical simulation. After this simulation, formations analyses of bands have been made using many steps in each test specimen and, then, comparing this same formation between the test specimen with geometries of different notches. At last, it has been checked that as much the formation of shear bands as the characteristics of fracture in the studied material are directly related with the geometrical shape of the notch.